Turnover Intention: The Moderating Role of Affective Commitment on Leadership and Engagement at PT Natura Pesona Mandiri Bali - I Gede Putu Brahmantta Bismahogra Budisw; Suci, Ni Made (Amkop Management Accounting Review (AMAR), 2026)
This research examines the effects of transformational leadership and employee engagement on turnover intention, moderated by affective commitment. It adopts an explanatory method to investigate causal links between variables and validate the formulated hypotheses. The population comprises all 70 employees at PT Natura Pesona Mandiri, sampled entirely through a census (total sampling) technique. Data collection occurred from September 2024 to February 2025 via structured questionnaires distributed on Google Forms, employing an ordinal scale. Analysis was conducted using Partial Least Squares Structural Equation Modeling (SEM-PLS) in SmartPLS software, including outer model checks for validity and reliability, and inner model tests for hypotheses via 5,000-resample bootstrapping. Findings reveal that transformational leadership lacks a significant direct impact on turnover intention, but employee engagement significantly reduces it negatively. These outcomes highlight affective commitment's vital role in bolstering leadership and engagement efficacy to lower turnover intention, alongside confirming transformational leadership's indirect contribution to employee retention.